The quality of care in homes for the aged in the South West Cape region as measured by tracer methodology and recommendations for improving, surveying and monitoring medical, nursing and psychosocial service rendering - Whittaker, Stuart (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.D.) -- University of Stellenbosch, 1991.